Role of MMP-9 and NF-κB in Diabetic Retinopathy: Progression and Potential Role of Bioflavonoids in the Mitigation of Diabetic Retinopathy - Ritu; Goyal, Ramesh K.; Narwal, Sonia; Bhatt, Alok; Sehrawat, Renu; Devi, Pooja; Gulati, Monica; Singla, Rajeev K. (Current Medicinal Chemistry, 2025)
“Diabetes mellitus” is a chronic metabolic disorder manifested by elevated blood glucose levels, primarily due to insufficient insulin production or resistance to insulin. Long-term diabetes results in persistent complications like retinopathy, cardiomyopathy, nephropathy, and neuropathy, causing significant health risks. The most alarming microvascular consequence allied with diabetes is “diabetic retinopathy,” distinguished by the proliferation of anomalous blood vessels in the eye, mainly in the retina, resulting in visual impairment, diabetic macular edema, and retinal detachment if left untreated. According to estimates, 27.0% of people with diabetes worldwide have retinopathy, which leads to 0.4 million blindness cases. It is believed that mitochondrial damage and the production of inflammatory mediators are the early indicators of diabetic retinopathy before any histological changes occur in the retina. Moreover, it is evident that augmented oxidative stress in the retina further initiates the NF-κB/MMP-9 downstream signaling pathway. Interestingly, these downstream regulators, Nuclear Factor Kappa B [NF-kB] and matrix metalloproteinases 9 [MMP-9], have been recognized as important regulators of the inception and advancement of diabetic retinopathy. This diabetes and oxidative stress-induced MMP-9 are believed to regulate various cellular functions, including angiogenesis and apoptosis, causing blood-retinal barrier breakdown and tight junction protein degradation that further leads to diabetic retinopathy. Thus, there is an emergency need for the treatment of diabetic retinopathy. Emerging treatment options include anti-VEGF, laser treatment, and eye surgery, but these have certain limitations. This comprehensive review explores the mechanisms of MMP-9 and NF-kB involvement in diabetic retinopathy and bioflavonoids' therapeutic potential and mechanisms of action in inhibiting MMP-9 activity and suppressing NF-kB-mediated inflammation. Clinical evidence supporting the use of bioflavonoids in mitigating diabetic complications and future perspectives are also examined.
Keywords: Diabetes